Pengaruh gratis ongkos kirim dan cash on delivery (COD) terhadap keputusan pembelian pada pengguna e-commerce lazada di Surabaya - Anggraini, Listiana; Supriyono, Supriyono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
In this era of digital industry, the development of technology and information systems greatly influences consumer behavior. The role of technology is also growing in line with the development of human life. Relationships between fellow humans that continue to develop in various parts of the world are also facilitated by the rapid development of technology and information in various fields today. Lazada is one of the information technologies that makes it easier for consumers to shop online. This study aims to determine the effect of Free Shipping and Cash On Delivery (COD) on Purchasing Decisions on Lazada E-Commerce users in Surabaya. This study uses a quantitative approach method. This study uses Lazada users as the population. While the research sample is Lazada E-Commerce users in Surabaya. The researcher uses a non-probability sampling calculation method with a purposive sampling technique. The data collection technique uses a questionnaire with a total of 130 respondents consisting of ages 17-35 years. The data is then analyzed using SmartPLS 3.0. The results of the study show that Free Shipping has a significant positive effect on Purchasing Decisions. This means that the more free shipping promotions given by Lazada, the higher the level of purchasing decisions. Cash On Delivery (COD) has a significant positive effect on Purchasing Decisions. This means that the Cash On Delivery (COD) payment method increases purchasing decisions on the Lazada application.